Breathing therapy and emotional freedom techniques on public speaking anxiety in Turkish nursing students: A randomized controlled study - ÖZÇELİK, SEMANUR KUMRAL (Elsevier Inc., 2020)
Background and objective: Public speaking is a common challenge that university students have to face. This study aims to determine the effects of Breathing Therapy and Emotional Freedom Techniques (EFT) on public speaking anxiety in Turkish nursing students. Methods: This randomized controlled study included 76 nursing students. Data were collected using the Descriptive Characteristics Form, Subjective Units of Disturbance Scale, The State-Trait Anxiety Inventory, and the Speech Anxiety Scale. Results: Before the administration of Breathing Therapy and EFT, the students’ median scores from the Subjective Units of Disturbance Scale, the State-Trait Anxiety Inventory, and the Speech Anxiety Scale were similar. However, the median scores of the Subjective Units of Disturbance Scale, the State-Trait Anxiety Inventory, and the Speech Anxiety Scale scores significantly decreased in both of the experimental groups after the interventions (p <0.001). EFT (d = 3.18) was more effective than Breathing Therapy (d = 1.46) in reducing Speech anxiety. Conclusion: It was found that Breathing Therapy and EFT are effective methods to reduce stress, anxiety, and speaking anxiety. © 2020
Keywords: Anxiety; Emotional freedom techniques; Nurses; Nursing students; Public speaking; Stress